Visualization of Zika Virus Infection via a Light-Initiated Bio-Orthogonal Cycloaddition Labeling Strategy - Zheng, Judun; Yue, Rui; Yang, Ronghua; Wu, Qikang; Wu, Yunxia; Huang, Mingxing; Chen, Xu; Lin, Weiqiang; Huang, Jialin; Chen, Xiaodong; Jiang, Yideng; Yang, Bin; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Zika virus (ZIKV) is a re-emerging flavivirus that leads to devastating consequences for fetal development. It is crucial to visualize the pathogenicity activities of ZIKA ranging from infection pathways to immunity processes, but the accurate label-ing of ZIKV remains challenging due to the lack of a reliable labeling technique. Herein, we introduce the photo-activated bio-orthogonal cycloaddition to construct a fluorogenic probe for the labeling and visualizing of ZIKV. Via a simple UV photoirradiation, the fluorogenic probes could be effectively labeled on the ZIKV virus. We demonstrated that it can be used for investigating the interaction between ZIKV virus and diverse cells, and avoiding the autofluorescence phenomenon in traditional immunofluorescence assay. Thus, this biorthogonal-enabled labeling strategy can serve as a promising approach to monitor and understand the interaction between the ZIKV virus and host cell.